Research of total-focusing-imaging based on phase coherence and dB amplitude enhancement - Nian Kun Pan; Bin Shao; Hua Chun Fang (AIP Advances)
To address the issue of weak defect visualization in the ultrasonic total-focusing method (TFM) after denoising, this paper integrates Phase Coherence Imaging (PCI) and dB amplitude enhancement (dB) with the TFM. This combination improves image accuracy and makes defects in the image more distinguishable. First, a carbon steel block model with holes as defects at different locations was established using COMSOL finite element software. The effects of different probe parameters on TFM, TFM-PCI, and TFM-PCI-dB imaging of the carbon steel block were studied to identify the optimal probe parameters. Then, the study compared the denoising and artifact removal effects of TFM-average denoising, TFM-dB, TFM-PCI, and TFM-PCI-dB imaging methods. For TFM or PCI, results suggested that higher probe frequencies led to higher imaging accuracy and more detailed information, while the probe element spacing had little impact on imaging accuracy. An increased number of elements and larger element spacing covered a wider area, providing more comprehensive image information. However, for the TFM-PCI-dB method, results suggested that it can better remove noise and artifacts from the image, while also enhancing the amplitude of defects in the image, thereby improving the accuracy of the image. Simulation and experimental results indicate that the TFM-PCI-dB method enhances detection accuracy, providing valuable insights for high-precision defect detection.